2014
DOI: 10.1111/jbi.12323
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast phylogeography of the East Asian Arcto‐Tertiary relict Tetracentron sinense (Trochodendraceae)

Abstract: Aim A phylogeographical study of the widespread but phylogenetically isolated East Asian endemic tree species Tetracentron sinense (Trochodendraceae) was performed to evaluate whether and how Pleistocene and pre‐Pleistocene climate changes helped to influence current phylogeographical patterns, and to describe the current patterns of genetic diversity and their implications for conservation. Location Southwestern and central subtropical China. Methods Sequences of four chloroplast spacer regions were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 73 publications
(94 reference statements)
8
68
0
1
Order By: Relevance
“…Similar results have been reported on Rosa praelucens, Coptis teeta, Reaumuria soongarica and Miscanthus sinensis (Guan et al 2012, Yang et al 2013, Xiao et al 2013. Meanwhile, the results from cpDNA marker in T. sinense also showed that phenotypic variation mainly resulted from the variation among populations (Sun et al 2014). The cause may be correlated to the distinctive environment in different populations.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Similar results have been reported on Rosa praelucens, Coptis teeta, Reaumuria soongarica and Miscanthus sinensis (Guan et al 2012, Yang et al 2013, Xiao et al 2013. Meanwhile, the results from cpDNA marker in T. sinense also showed that phenotypic variation mainly resulted from the variation among populations (Sun et al 2014). The cause may be correlated to the distinctive environment in different populations.…”
Section: Discussionsupporting
confidence: 81%
“…Among the 11 populations of T. sinense, the CV of phenotypic traits in WFHH was the highest, indicating the relatively abundant phenotypic diversity, which was in consistent with the result from cpDNA marker (Sun et al 2014). The reason may be correlated to the geographical position and topography.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In particular, patterns of plant dispersal/migration have emerged, such as north-to-south migration to the Himalaya-Hengduan Mountains for some ArctoTertiary floristic elements (H. Sun, 2002a, b; Y. X. Sun et al, 2014), migration from Southwest China to other regions along mountain corridors for numerous groups containing taxa distributed across East Asia (Wang, 1992), migration from South China to Southeast Asia for some genera distributed in the subtropics and tropics Wen, 2013, 2014), and migration between East China and Japan via the exposed East China Sea land bridge for some herbs, shrubs and trees with disjunct distributions in these areas (Qiu et al, 2009a(Qiu et al, , b, c, 2011Sakaguchi et al, 2012). The driving mechanisms of species divergence in the SJFR have been widely discussed.…”
Section: Introductionmentioning
confidence: 99%